India’s Trade Intensity with ASEAN Countries - Acharya, Rekha; Sharma, Haldhar (Journal of Commerce and Trade, 2012)
India is a growing economy and ASEAN is a fastest developing trade block. India’s trade relations with ASEAN substantially have been changed after the “Look-East” policy of India in 1991. To strengthen the economic relation with ASEAN; India became full dialogue partner of ASEAN in December 1995 at Bangkok. More recently a Free Trade Agreement in goods was signed between India and ASEAN, in Bangkok on August 13th 2009. In this context, this paper is an attempt to measure the India’s trade intensity indices of export and import with ASEAN. For calculation of these indices few economic variables have been considered such as export, import, world export and world import. Trend analysis and dummy variable have been used to measure the trend and impact of India’s full dialogue partnership with ASEAN. Study indicates that India’s trade is increasing with ASEAN countries, while India’s trade intensity of export and import is not up to the desired level with Philippines and Thailand countries of ASEAN. India’s full dialogue partnership is not able to influence India’s trade intensity of export, while it is significantly affecting India’s trade intensity of import with Indonesia, Malaysia, Singapore and Thailand except Philippines.